Race and political theology - Lloyd, Vincent; Anidjar, Gil (Stanford University Press, 2012)
Political theology and the case of Otto Brunner / Vincent P. Pecora -- "The politicization of heaven" : Wilhelm Stapel's political theology of nationalist sovereignty / Christoph Schmidt -- Between W.E.B. Du Bois and Karl Barth : the problem of modern political theology / Kameron Carter -- There are no clean souls : the promise and perils of political theology in The souls of black folk / Jonathon S. Kahn -- The race for theology : toward a critical political theology of freedom / Corey D.B. Walker -- The enemy's two bodies (political theology too) / Gil Anidjar -- The double mark of the male Muslim : eracing Othello / Daniel Boyarin -- Between sacred and secular : Michael Walzer's exodus story / Bonnie Honig -- The state between race and religion : a conversation / Martin Land and Jonathan Boyarin -- From political theology to vernacular prophecy : rethinking redemption / George Shulman